Effects of Insoluble Fiber Source (Cellulose or Distillers Dried Grains with Solubles) on Growth Performance of Nursery Pigs - H. S. Cemin; M. D. Tokach; S. S. Dritz; J. C. Woodworth; J. M. DeRouchey; R. D. Goodband (Kansas Agricultural Experiment Station Research Reports, 2018)
A total of 3,171 weanling pigs (PIC 327 × L42) with an initial body weight (BW) of 12.7 lb were used in a 39-d study with 66 or 67 pigs per fence-line feeder (experimental unit) and 12 replicates per treatment. Pens were blocked by BW and allotted to 1 of 4 dietary treatments in a randomized complete block design. The treatment structure was a 2 × 2 factorial with 0 or 1% cellulose (Arbocel, J. Rettenmaier USA, Schoolcraft, MI) and distillers dried grains with solubles (DDGS; 0 or 5% in Phase 1 and 0 or 15% in Phase 2). Dietary phases 1 and 2 were offered from d 0 to 10 and 10 to 25, respectively. From d 25 to 39, pigs received a common diet with 25% DDGS. Growth performance, pig removals, and economic variables were evaluated. From d 0 to 25, there was an interaction between cellulose and DDGS (P= 0.040) for average daily gain (ADG). Pigs fed diets with DDGS and cellulose had lower ADG than those fed diets without DDGS, with pigs fed diets with DDGS without the addition of cellulose having intermediate ADG. From d 25 to 39, there was a marginally significant interaction (P= 0.080) for average daily feed intake (ADFI). Pigs previously fed diets without DDGS and with cellulose had higher ADFI than those fed diets with DDGS and cellulose, and pigs previously fed diets without cellulose had similar ADFI regardless of DDGS inclusion. In the overall period (d 0 to 39), there was an interaction between cellulose and DDGS (P= 0.021) for ADG, similar to d 0 to 25. There was a marginally significant interaction (P= 0.070) for pig removals. Adding cellulose to diets without DDGS resulted in numerical decrease in pig removals, but the inclusion of cellulose to diets with DDGS resulted in increased pig removals. For economics, an interaction was observed between cellulose and DDGS for income over feed cost (IOFC;P= 0.014). Pigs fed diets without DDGS and with the addition of cellulose had higher IOFC compared to pigs fed diets with DDGS and cellulose, with other treatments being intermediate. In summary, the addition of cellulose to diets without DDGS resulted in slight improvements in pig removals and economic variables, with no evidence of impact on growth performance. The reduction in performance observed when cellulose was added to diets that contained DDGS may be due to a negative effect of the high fiber level.
Keywords: cellulose; distillers dried grains with solubles; growth; swine